Development and Application of a Revit-ANSYS Model Transformation Interface. Issue 7 (October 2021) - Zhou, H; He, X; Leng, X L
Abstract: To address the difficulties of modeling complex building structures in ANSYS, the Revit-ANSYS model conversion interface was developed. As powerful 3-d modeling software, Revit can establish refined and complex models, which has advantages that ANSYS does not have. It is particularly important to automatically transform BIM complex model into structural analysis model for accurate structural calculation and analysis. Based on the Revit application programming interface (API), the geometry size, coordinates, material attributions, boundary conditions and load information of the existing structural models in Revit, were extracted using C# on the Visual Studio 2017 platform for secondary development. In the interface program, all the required information was processed, material attributes were matched, structural connection was conducted using Boolean operation, and mesh division was prepared in advance, with the purpose of automatic modeling, Boolean operation, and automatic mesh division before finite element analysis using ANSYS. This generated an APDL file that can be recognized by ANSYS for this purpose. The rapid transformation of Revit-ANSYS model was thus realized. The conversion interface sets up the data communication between Revit and ANSYS and is applicable to both superstructure and underground structure. The goal of importing complex structure models of Revit into ANSYS for accurate structural calculation and analysis was achieved. This improved the efficiency of modeling and calculation of complex structures. The resulting Revit-ANSYS model conversion interface can integrate the two different software packages to create BIM and FEM models. Finally, it was applied to the 3-d BIM modeling and structural analysis of a construction project. By using the interface program, the construction was dynamically simulated by real-time updating of BIM model and the mechanical calculation was conducted. The correctness and practicability of the model conversion interface were verified.